Frequency of Hepatitis C in Patients Undergoing Ophthalmic Surgeries; A Multicenter Study - Sadiq, M. Ali A.; Naeem, Faiqa Jabeen; Ali, Mehreen Usman; Tayyab, Haroon; Jamshed, Saima; Malik, Irfan Qayyum; Qamar, Hafiz Muhammad; Hanif, Ayesha (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find the frequency of Hepatitis C in tertiary care hospitals in Gujranwala and Lahore. Study Design: Cross sectional observational study. Place and Duration of Study: Ophthalmology Departments of District Head Quarters Teaching Hospital Gujranwala and at Sardar Trust Eye Hospital, Garhi Shahu, Lahore for a duration of 12 months from March 2017 to March 2018. Material and Methods: A chart review of all patients admitted in the above mentioned hospitals was conducted. Patients with insufficient clinical information documented in hospital record were excluded from the study. Status of each of the patient whether Hepatitis C positive or not, was determined by the method of rapid chromatography immunoassay for qualitative detection. The results of all patients were recorded according to their age, sex and their demography. Results: The study was conducted on 4968 patients admitted for ophthalmic surgeries above the age of 13 years. There were 1003 patients at DHQ Hospital Gujranwala and 3965 at Sardar Trust Eye Hospital. Out of 1003, 548 patients (54.6%) were male and 455 (45.3%) were female. 189 patients turned out to have Hepatitis C having a prevalence of 18.8%. However, at Sardar Trust Eye Hospital, out of 3965 patients admitted, 2914 (73%) were male, and remaining (27%) were female. 418 patients were found to be Hepatitis C positive, which constituted about 10.5% of all patients in Lahore. Conclusion: Frequency of Hepatitis C was 18% in Gujranwala with female dominance and 10.5% in Lahore with male predominance